2020
DOI: 10.1002/iid3.373
|View full text |Cite
|
Sign up to set email alerts
|

Five immune‐gene‐signatures participate in the development and pathogenesis of Kawasaki disease

Abstract: Objective To screen for immune genes that play a major role in Kawasaki disease and to investigate the pathogenesis of Kawasaki disease through bioinformatics analysis. Methods Kawasaki disease‐related datasets GSE18606, GSE68004, and GSE73461 were downloaded from the Gene Expression Omnibus database. Three microarrays were integrated and standardized to include 173 Kawasaki disease samples and 101 normal samples. The samples were analyzed using CIBERSORT to obtain the infiltration of 22 immune cells and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…Data at our center showed that there was no relationship between increased D dimer and IVIG resistance either, which is conflicted with reported studies ( 39 ). This may be associated with earlier IVIG treatment by 1 day in DDE, or it may be related to the differential expression of immune responsive genes during the KD occurrence and development ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data at our center showed that there was no relationship between increased D dimer and IVIG resistance either, which is conflicted with reported studies ( 39 ). This may be associated with earlier IVIG treatment by 1 day in DDE, or it may be related to the differential expression of immune responsive genes during the KD occurrence and development ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“… 15 We performed PCA to realine the dimensionality of the 24 types of immune infiltrating cells while retaining key information. 16 …”
Section: Methodsmentioning
confidence: 99%
“…A Doença de Kawasaki, também conhecida como síndrome de Kawasaki ou síndrome do linfonodo mucocutâneo, é uma doença pediátrica exantemática febril aguda, apresentando-se principalmente com lesões de vasculite sistêmica (NIE H, et al, 2021). Embora a DK tenha sido originalmente relatada como autolimitada e benigna, hoje é reconhecida como uma vasculite sistêmica com predileção específica por formar lesões nas artérias coronárias (KANEKO K, et al, 2020; PADILLA LA, et al, 2021).…”
Section: Revisão Bibliográfica Definição E Epidemiologiaunclassified